A linear heterometallic bismuth-copper coordination polymer containing two types of organic ligands - Yue, Z.L.; Feng, Y.Q.; Ng, S.W. (International Union of Crystallography, 2015)
In the linear coordination polymer catena-poly[[[aqua(1,10-phenanthroline-κ2 N,N')copper(II)]-μ-pyridine-2,6-dicarboxylato-κ4 O2:O2',N,O6-[(nitrato-κ2 O,O')bismuth(III)]-μ-pyridine-2,6-dicarboxylato-κ4 O2,N,O6:O6'] dihydrate], {[BiIIICuII(C7H3NO4)2(NO3)(C12H8N2)(H2O)]·2H2O} n , the BiIII cation is O,N,O'-chelated by the two pyridine-2,6-dicarboxylate ligands and O,O'-chelated by the nitrate anion, the nine coordinating atoms conferring a tricapped trigonal prismatic environment on the metal centre. Each pyridine-2,6-dicarboxylate ligand uses one of its carboxylate O atoms to bind to an aqua(1,10-phenanthroline)copper(II) unit, the Cu-O dative bonds giving rise to the formation of a ribbon motif. The CuII cation exhibits a square-pyramidal geometry. The ribbon motif propagates along the shortest axis of the triclinic unit cell and the solvent water molecules are hydrogen bonded to the same ribbon.